Sustainable University Strategy and Assessing Its Performance in Green Rankings - Saule Rakhmetullina; Ulan Nessipkaliyev; Olga Petrova; Darya Surova (Universitas Diponegoro, 2025)
The article explores the development of a sustainable university strategy and the assessment of its effectiveness using the international UI GreenMetric ranking system. Using the case of D. Serikbayev East Kazakhstan Technical University, the study demonstrates how the questionnaire-based criteria of the ranking can be integrated into the university’s strategic planning, educational processes, and administrative practices. The research employs a mixed-method approach, combining literature review, systems analysis, quantification of sustainability indicators, and data visualization. The findings show that transitioning from isolated environmental initiatives to a comprehensive, system-based strategy enables the university to achieve tangible sustainability outcomes and maintain its position in international rankings, even under limited resource conditions. The article also addresses the need to adapt ranking criteria to the national context and identifies directions for future research on the effective integration of the Sustainable Development Goals (SDGs) into the university setting.